Mesoporous ZnCo2O4/rGO nanocomposites enhancing sodium storage. (25th March 2019) - Xu, Jie; Yan, Bo; Maleki Kheimeh Sari, Hirbod; Hao, Youchen; Xiong, Dongbin; Dou, Shuming; Liu, Wen; Kou, Huari; Li, Dejun; Li, Xifei
Abstract: In this study, mesoporous ZnCo2 O4 /rGO nanocomposites were favorably synthesized via a simple solvothermal technique. As a prospective anode material for sodium-ion batteries, the resulting ZnCo2 O4 /rGO-II nanocomposite exhibited superior electrochemical sodium storage performance with predominant specific capacity, favorable cyclability and ascendant rate capability. For example, an outstanding discharge capacity of 210.5 mAh g −1 was delivered at a current density of 200 mA g −1 . Notably, the nanocomposite could yield a discharge capacity of 101.7 mAh g −1 at a current density of 1000 mA g −1 after 500 loops, which certifies its superior capacity retention and predominant cycling stability. The boosted performance of the anode materials is due to the mutual synergistic effect resulting from a combination of the mesoporous ZnCo2 O4 nanospheres and conducting reduced graphene oxide nanosheets.